The fructan syndrome: Evolutionary aspects and common themes among plants and microbes - TOKSOY ÖNER, EBRU (WILEY, 2018)
Fructans are multifunctional fructose-based water soluble carbohydrates found in all biological kingdoms but not in animals. Most research has focused on plant and microbial fructans and has received a growing interest because of their practical applications. Nevertheless, the origin of fructan production, the so-called fructan syndrome, is still unknown. Why fructans only occur in a limited number of plant and microbial species remains unclear. In this review, we provide an overview of plant and microbial fructan research with a focus on fructans as an adaptation to the environment and their role in (a)biotic stress tolerance. The taxonomical and biogeographical distribution of fructans in both kingdoms is discussed and linked (where possible) to environmental factors. Overall, the fructan syndrome may be related to water scarcity and differences in physicochemical properties, for instance, water retaining characteristics, at least partially explain why different fructan types with different branching levels are found in different species. Although a close correlation between environmental stresses and fructan production is quite clear in plants, this link seems to be missing in microbes. We hypothesize that this can be at least partially explained by differential evolutionary timeframes for plants and microbes, combined with potential redundancy effects. The capacity to biosynthesize fructans, fructose-based oligo and polysaccharides, is scattered over certain plant and microbial families. This review represents the first attempt to grasp the overall meaning of the fructan syndrome, crossing plants and microbes. By highlighting functional similarities and differences, this review prepares the ground for further research in plants and microbes, with focus on water scarcity and fructan signalling as common themes.
Keywords: ABIOTIC STRESS TOLERANCE; SNOW MOLD RESISTANCE; HYDROLASE FAMILY 32; HIGH DP FRUCTAN; STREPTOCOCCUS-MUTANS; FREEZING TOLERANCE; FUNCTIONAL-ANALYSIS; LEVAN PRODUCTION; SUCROSE 1-FRUCTOSYLTRANSFERASE; STRUCTURAL-CHARACTERIZATION